A Review on Nanoparticle-Based Drug Delivery Systems for Treating Placental Dysfunction: Review Article (Journal of Pharma Insights and Research, 2024)
The placenta plays a significant role during pregnancy. Preeclampsia and fetal growth restriction are two serious obstetric complications influenced by placental dysfunction. Currently, prophylaxis is often administered too late to avoid disease manifestation, and there is no effective treatment for placental dysfunction during the perinatal period. However, with the recent integration of nanoscience and medicine, it is anticipated that innovative and effective nanotherapies will be developed to address the difficulty of managing placental dysfunction. Nanoparticle drug delivery is now safe and precise, utilizing intelligent nanoparticles capable of loading drugs, ligands, and other therapeutic substances specifically targeted at the placenta. Placental malfunction seriously jeopardizes maternal and fetal health, frequently resulting in issues such as intrauterine growth restriction and preeclampsia. This article provides an introduction to nanoparticles in medicine, types of nanoparticles used, targeted drug delivery systems, benefits of nanoparticles in medicine, challenges and limitations, and applications in specific diseases. As conventional treatment options are limited, creative methods are needed to improve results. Due to their special physicochemical characteristics and ability to pass through biological barriers, nanoparticles have become attractive options for targeted drug administration